A thermodynamic model for the simultaneous charge/spin order transition in LaCu3Fe4O12 - Allub, Roberto Jose (2012)
LaCu3Fe4O12 undergoes a phase transition at 393 K from an antiferromagnetic insulating state at low temperatures to a paramagnetic metallic state above the critical temperature. We build a basic model for the electronic structure of this material that allows us to extract the mechanism that governs the transition and calculate the stability of the different phases. It also allows us to speculate on the effect of pressure on this material to build a T–p phase diagram.